Roles of cell differentiation factors in preimplantation development of domestic animals - Ken SAWAI (The Society for Reproduction and Development, 2021)
In mammalian embryos, the first visible differentiation event is the segregation of the inner cell mass (ICM) and trophectoderm (TE) during the transition from the morula to the blastocyst stage. The ICM, which is attached to the inside of the TE, develop into the fetus and extraembryonic tissues, while the TE, which is a single layer surrounding the fluid-filled cavity called the blastocoel, will provide extraembryonic structures such as the placenta. ICM/TE differentiation is regulated by the interaction between various transcriptional factors. However, little information is available on the segregation of the ICM and TE lineages in preimplantation embryos of domestic animals, such as cattle and pigs. This review focuses on the roles of cell differentiation factors that regulate the ICM/TE segregation of preimplantation bovine and porcine embryos. Understanding the mechanism of cell differentiation in early embryos is necessary to improve the in vitro production systems for bovine and porcine embryos.